HEAT TRANSFER MODELING IN SOLAR COLLECTOR ABSORBER WITH PHASE CHANGE MATERIAL - Aliuly, A.; Karlina Е.; Yerdesh Е.; Mohanraj М.; Belyayev Е. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
A numerical model has been proposed in this work for predicting the energy performances of the solar channel absorber plate under Kazakhstan climates. The numerical model is based on energy and mass balance. A new solar channel absorber plate configuration is proposed to improve the performance. A comparison of results has been made between the conventional solar absorber plate and solar channel absorber plate with PCM. The numerical simulation was performed for wide range of ambient temperatures of continental climate with wide range of solar intensities between 100 W/m2 and 900 W/m2. The influences of solar intensity and ambient temperature are discussed. The proposed technology can be used in the following systems: solar water heater, solar assisted air/ground source heat pump, solar thermal energy storage. The developed calculation algorithm based on the heat balance can be used to simulate the thermal performance of solar thermal collectors of various configurations. Various PCMs will be considered in future research, in the heat storage tank.